Assessment of self-efficacy beliefs and academic performance for sources and implications in high and low achieving secondary schools in Mbarara district, Uganda - Kemeza, Imelda; Kibanja, Milly Grace; Steffens, Karl (International Journal of Advance Research, Ideas and Innovations in Technology, 2020)
The major purpose of the study was to assess the relationship between self-efficacy beliefs and academic performance between high and low achieving secondary schools in Mbarara District. The study also explored the sources related to the academic gap that informed implications towards narrowing the academic gap between high and low achieving secondary schools. The study was mainly quantitative and used the sequential explanatory paradigm. Questionnaires were used to gather data from three hundred participants. Interview responses were analyzed to supplement the information collected through the questionnaire. Data were analyzed using the computer package known as Statistical Package for the Social Sciences version 20. The findings of the study showed that there are very weak negative correlations between self-efficacy beliefs and academic performance in low achieving secondary schools r (148) = -.163, p=.047) while high achieving have weak corrections r (148)= -0.203, p=.013) which is significant. The study, therefore, recommends that students could be encouraged to practice adherence to moral self-sanctions while teachers evaluate and consult on performance so that students gain confidence and assurance to achieve academic success. Furthermore, the findings of the study have sources for differences in principal passes that effect inequitable admission to public universities. Also, the findings informed implications towards narrowing the academic performance gap between high and low achieving secondary schools.
Keywords: Assessment; Self-Efficacy Beliefs; Academic Performance; Sources; Implications; Achieving